Vitamins and hormones : advances in research and applications. - Harris, Robert S. (Robert Samuel), 1904-1983; Marrian, G. F.; Thimann, Kenneth Vivian, 1904-1997 (Vitamins and hormones, 1958)
VITAMINS AND HORMONES V16.